Treatment outcome of pediatric acute lymphoblastic leukemia in Yeungnam region: Multicenter retrospective study of Study Alliance of Yeungnam Pediatric Hematology-Oncology (SAYPH). (19th May 2018) - Yang, Eu Jeen; Park, Kyung Mi; Lee, Jae Min; Hah, Jeong Ok; Park, Sang Kyu; Suh, Jin Kyung; Kim, Ji Yoon; Lee, Kun Soo; Park, Jikyoung; Park, Eun Sil; Lim, Jaeyoung; Shim, Ye Jee; et al.
Abstract: Objectives: We aimed to evaluate treatment outcomes of pediatric acute lymphoblastic leukemia (ALL) subgroups by risk–stratification, in the Yeungnam region of Korea.Methods: We reviewed the courses of 409 newly diagnosed ALL patients from January 2004 to December 2013 in the Yeungnam region.Results: All patients were classified into three risk groups: standard risk (SR, n=212), high risk (HR, n=153) and very high risk (VHR, n=44). The mean follow-up time was 73.6 ± 39.4 months. The 7-year event-free survival (EFS) and overall survival (OS) rates were 78.7 ± 2.1% and 86.8 ± 1.8%, respectively. Significant 7-year EFS and OS rates for SR (84.0 ± 2.7%, 93.7 ± 1.8%), HR (76.5 ± 3.5%, 82.1 ± 3.3%), and VHR (60.6 ± 7.5%, 69.9 ± 7.5%) were observed (P<0.001), respectively. Relapse occurred in 52 patients, and the cumulative 7-year incidence of relapse differed according to risk groups (SR vs. HR vs. VHR=12.6% vs. 14.0% vs. 29.6%, P=0.003).For the 46 relapsed patients who were treated, the 3-year EFS and OS were 42.3 ± 8.3%and 46.4± 8.4%. Among the 44 VHR patients, EFS was not significantly different between the chemotherapy-treated patients and those received hematopoietic stem cell transplantation (P=0.533). The 7-year EFS of the hyperleukocytosis subgroup (24 cases, 14 under 10 years of age)showed a tendency for better prognosis than that of the other VHR subgroups (P=0.178).Conclusion: Our results revealed improved outcomes in pediatric ALL patients with risk-stratified therapy. The hyperleukocytosis subgroup without any combined chromosomal abnormalities may respond favorably to chemotherapy alone after first complete remission.